Investigation into the Adsorption of Methylene Blue and Methyl Orange by UiO-66-NO2 Nanoparticles - Hien Thi Dinh; Nam Trung Tran; Dai Xuan Trinh (Journal of Analytical Methods in Chemistry)
In this work, the adsorptive removal of methylene blue and methyl orange by UiO-66-NO2 nanoparticles was studied. The influence of pH on the adsorption capacity was assessed. The kinetics of the adsorption process were investigated and compared with pseudo-first-order, pseudo-second-order, Elovich, and intraparticle models. The kinetics of the adsorption fits moderately with the pseudo-first-order, but perfectly fits with pseudo-second-order models, and has a very good fit with the Elovich and intraparticle models. The adsorption isotherms were measured and compared with the Langmuir and Freundlich models. The adsorption capacity of methyl orange (MO) on UiO-66-NO2 nanoparticles (142.9 mg/g) was over three times higher than that of methylene blue (MB) on the nanoparticles (41.7 mg/g). The discrepancy between these capacities was attributed to the presence of the -NO2 functional group, which caused a strong negative mesomeric effect in the metal-organic framework structure.